PERKEMBANGAN PENDIDIKAN KABUPATEN BENGKULU SELATAN PASCA PEMEKARAN TAHUN 2003-2018 - Jely Novianti; Bedriati Ibrahim; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The development of a nation cannot be separated from the role of government and society, this development will never stop, the process will recognize a change. Education is an absolute need that must be met by humans throughout life. Without education, it is absolutely impossible for a group of people to live to develop in line with the aspirations for advancement, prosperity and happiness according to their concept of life view. What about good the education system is in Indonesia cannot be separated from the role of the regions, all of this is because only local people know best what their regional needs are. Autonomy and decentralization have very fundamental consequences for future educational activities in Indonesia. The purpose of this research is to (1) Knowing the history of the development of South Bengkulu Regency in 2003. (2) Knowing the development of education in South Bengkulu district after the division in 2003-2018. (3) Knowing the driving and inhibiting factors in the development of education in South Bengkulu district after the division in 2003-2018. In this study, the authors use the historical method, namely a set of principles and rules that provide effective assistance to collect materials for historians, assess critically and then produce a synthesis of the results in written form. The results of this study indicate that the development of education in South Bengkulu Regency is not too significant, this is because South Bengkulu Regency has had adequate facilities since the beginning of its expansion in 2003 where South Bengkulu Regency is in the highest position. the parent district of the other two districts.Key Words: Development, Education, Autonomy and Decentralization